LYCOPENE IN THE MANAGEMENT OF ORAL SUBMUCOUS FIBROSIS - Panneer Selvam, Niranzena; Dayanand, Arjun Anand (Asian Journal of Pharmaceutical and Clinical Research, 2013)
Background: Oral Submucous Fibrosis is a potentially malignant disorder well known for its chronic and resistant nature. The conservative drug treatment that is currently available for this disorder is clearly inadequate. The aim of the study was to evaluate the efficacy of oral lycopene therapy when used in combination with conventional intralesional steroid therapy in the management of oral submucous fibrosis. Methods: Forty five patients with oral submucous fibrosis (grade III and IV) were included under the study and were randomly divided into 3 groups consisting of 15 cases each: Group A (oral lycopene 16 mg/day with biweekly intralesional steroids and hyaluronidase), Group B (oral antioxidant capsules with biweekly intralesional steroids and hyaluronidase) and Group C (biweekly intralesional steroids and hyaluronidase alone). Mouth opening and burning sensation were recorded from baseline to 6 weeks. Cases were followed up to 3 and 6 months. Results: There was significant increase in mouth opening among all the 3 groups. The results were statistically significant between Group A and C and Group B and C. Conclusion: Lycopene in combination with intralesional steroids and Hyaluronidase, is highly efficacious in improving the mouth opening and reducing other symptoms in patients with Oral Submucous Fibrosis. No side effects were reported with its usage.